Building relationships through integrated online media platforms: Analysis of top 100 global brands - SHIN, Wonsun (Institutional Knowledge at Singapore Management University, 2015)
Many studies have examined organizations’ use of specific types of online media, but few studies have examined how organizations generate dialogues and develop relationships by using multiple online communication platforms. This study takes an integrated approach by examining how top global organizations incorporate brand Web sites, Facebook, and Twitter to cultivate relationships with stakeholders. Its findings suggest that those particular online media are used similarly, that is, more for information dissemination than user engagement and more for one-way than two-way communication. The findings also suggest that the types of products promoted can affect the way that organizations use different online media to develop relationships.